PENGELOLAAN LIMBAH TERNAK BABI MENJADI PUPUK ORGANIK UNTUK MENDUKUNG PERTANIAN ORGANIK - Puja, I .N.; Ratna Adi, I. G.P.; Sumardani, N.L.G.; Dyatmikawati, P. (Buletin Udayana Mengabdi; Vol 16 No 1 (2017), 2018)
In Puhu Village is one of the pig farming centers and will generate 4.160 tons of waste waste every day. This livestock waste smells unpleasant and pollute the environment, can interfere with human health and comfort so that need to get handled. This activity is carried out with method of technology transfer approach and entrepreneurial spirit development, while its implementation is applied by counseling method, training, mentoring and comparative study. The result of a farmer's activity in Puhu Village has been a pioneer in processing pig waste into organic fertilizer. The organic fertilizer produced contained C-organic content of 38.99% (Very High), N content of 0.53% (High), P content available 108.09 ppm (Very High), K-available 6915.33 ppm (Very Height) and DHL 6.52 mmhos/cm (Very High).